Early and innovative interventions for severe sepsis and septic shock: taking advantage of a window of opportunity - Rivers, Emanuel P. (Canadian Medical Association, 2005)
The pathogenic, diagnostic and therapeutic landscape of sepsis is no longer confined to the intensive care unit: many patients from other portals of entry to care, both outside and within the hospital, progress to severe disease. Approaches that have led to improved outcomes with other diseases (e.g., acute myocardial infarction, stroke and trauma) can now be similarly applied to sepsis. Improved understanding of the pathogenesis of severe sepsis and septic shock has led to the development of new therapies that place importance on early identification and aggressive management. This review emphasizes approaches to the early recognition, diagnosis and therapeutic management of sepsis, giving the clinician the most contemporary and practical approaches with which to treat these patients.